Respiratory activity and phenolic compounds in pre-cut celery - Viña, Sonia Zulma (2007)
The effect of temperature on respiratory activity and total phenol and flavonoid contents in pre-cut celery was assessed within the 24 h following this minimal processing. To this end, celery petioles were cut as strips, conditioned in crystal polyethylene terephthalate trays covered with PVC film and stored at 0, 10 and 20 °C. Samples were removed at 0, 2, 4, 6 and 24 h after processing to analyse respiratory activity and concentrations of total phenols and flavones. For the samples kept at 0 °C for 24 h, chlorogenic acid was also determined, along with total flavonoids and antioxidant power. At this temperature, the total phenol contents remained basically constant, though at 10 °C it increased considerably two hours after applying the cutting stress. At 20 °C the increase observed was less important. The flavones, identified by HPLC in pre-cut celery were apigenin and luteolin, whose concentrations also increased between two to six hours after processing. However, exposure for 24 h at 0 °C produced a considerable decrease in total flavonoids.